Analysis of Hall Sensor for Controlling the Speed of BLDC Motor Based E-Vehicle (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
The subject of this project, which focuses on the electric vehicle’s rear differential, is the examination of a high-performance brushless DC motor (BLDC) for an electric vehicle (EV) with Hall sensor control. Using a digital controller increases the drivsystem’s flexibility. A DC-DC Bidirectional Dual Converter is implemented to supply BLDC motors utilizing Smart Power Modules. The suggested system is set to operate at the required speed and receives Hall sensor signals from the motor. The experimental findings confirm the efficacy of the created drive operation. A brushless DC motor is widely used in many different sectors and solves many of the issues a brushed DC motor has. Creating the BLDCM control system necessitates low cost, a fast development cycle, outstanding control algorithm performance, and dependable operation. The idea behind this project is the BLDC motor speed control for an electric vehicle. The use of a digital controller increases the drivsystem’s flexibility. A Smart Power Module feeds The BLDC motor into the three-phase inverter. The experimental findings confirm the efficacy of the created drive operation.